Fractional modeling for prey and predator problem by using optimal homotopy asymptotic method - Biazar, Jafar; Safaei, Saghi; Tango, Martin (International Journal of Applied Mathematical Research, 2020)
In this paper, a fractional-ordered prey and predator population model is introduced and applied to obtain an approximate solution with help of optimal homotopy asymptotic method (OHAM). Some plots for populations of the prey and the predator versus time are presented to show the efficiency and the accuracy of the method and confirm that the method is straightforward as well. The fractional derivatives are described in the Caputo sense.Â